Angina and heart attack - Jevon, Philip (Facts (Oxford, England), 2012)
"Simple steps can be taken to help prevent angina getting worse, thus reducing the risk of a heart attack. The book helps patients and their families to understand the causes and risk factors for both angina and heart attacks, and it contains step-by-step, illustrated guidance on what to do if someone you know falls ill, including the recognition of symptoms and resuscitation, which can increase the chances of both an early admission to hospital and a favourable survival prognosis." -- Back book cover.